The Bright Future of Unconventional σ/π-Hole Interactions - Bauzá, Antonio; Mooibroek, Tiddo J.; Frontera, Antonio (Chemphyschem, 2015)
Non‐covalent interactions play a crucial role in (supramolecular) chemistry and much of biology. Supramolecular forces can indeed determine the structure and function of a host–guest system. Many sensors, for example, rely on reversible bonding with the analyte. Natural machineries also often have a significant non‐covalent component (e.g. protein folding, recognition) and rational interference in such ‘living’ devices can have pharmacological implications. For the rational design/tweaking of supramolecular systems it is helpful to know what supramolecular synthons are available and to understand the forces that make these synthons stick to one another. In this review we focus on σ‐hole and π‐hole interactions. A σ‐ or π‐hole can be seen as positive electrostatic potential on unpopulated σ* or π(*) orbitals, which are thus capable of interacting with some electron dense region. A σ‐hole is typically located along the vector of a covalent bond such as XH or XHlg (X=any atom, Hlg=halogen), which are respectively known as hydrogen and halogen bond donors. Only recently it has become clear that σ‐holes can also be found along a covalent bond with chalcogen (XCh), pnictogen (XPn) and tetrel (XTr) atoms. Interactions with these synthons are named chalcogen, pnigtogen and tetrel interactions. A π‐hole is typically located perpendicular to the molecular framework of diatomic π‐systems such as carbonyls, or conjugated π‐systems such as hexafluorobenzene. Anion–π and lone‐pair–π interactions are examples of named π‐hole interactions between conjugated π‐systems and anions or lone‐pair electrons respectively. While the above nomenclature indicates the distinct chemical identity of the supramolecular synthon acting as Lewis acid, it is worth stressing that the underlying physics is very similar. This implies that interactions that are now not so well‐established might turn out to be equally useful as conventional hydrogen and halogen bonds. In summary, we describe the physical nature of σ‐ and π‐hole interactions, present a selection of inquiries that utilise σ‐ and π‐holes, and give an overview of analyses of structural databases (CSD/PDB) that demonstrate how prevalent these interactions already are in solid‐state structures. Strange attractions: Unconventional σ‐ and π‐hole interactions are approached from three perspectives, namely their physical nature, their experimental exploitation and their prescence in databases of solid‐state structures (CSD/PDB). These data highlight that unusual σ‐ and π‐holes are very similar to more conventional ones (e.g. hydrogen bonding) and are capable of influencing the structure and function of molecular systems.